Flexible optoelectronic neural transistors with broadband spectrum sensing and instant electrical processing for multimodal neuromorphic computing. Issue 2 (2nd November 2022) - Ni, Yao; Yang, Lu; Feng, Jiulong; Liu, Jiaqi; Sun, Lin; Xu, Wentao
Abstract: A flexible optoelectronic neural transistor (OENT) that consists of a one‐step spin‐coated tri‐blend film composed of 2, 7‐dioctyl[1]benzothieno[3, 2‐b][1]benzothiophene (C8‐BTBT), poly(3‐hexylthiophene‐2, 5‐diyl) (P3HT), and poly(methyl methacrylate) (PMMA) is demonstrated. The C8‐BTBT and P3HT phases in the film partially segregate into distinct domains, which combine to provide broadband spectrum sensing, and instant electrical‐processing capabilities dominated by C8‐BTBT. The OENT is sensitive to solar radiation from the near‐ultraviolet (NUV) and to visible (Vis) radiation from blue to red. When exposed to NUV radiation, the OENT responds sensitively and retains the memory of the exposure for over 10 3 s. The OENT provides a warning of excessive chronic exposure to harmful NUV. These properties allow high‐pass filtering with different cut‐off frequencies f c that can restrict the reception of blue, green, or red. These switchable f c enables sensitive image reconstruction and multitarget monitoring. The device combined with a chitosan gel achieves strictly defined short‐range plasticity of <1 s that can achieve diverse instant‐computing applications such as spatiotemporally correlated coding and logic functions. Stable real‐time signal processing facilitates the realization of a Morse‐code recognition system constructed using neuro‐morphological hardware, achieving highly accurate character recognition. This study provides a useful resource that can have applications in wearable biomedical electronics and multimodal neuromorphic computing. Abstract : Integration of multimode signal (e.g., optical and electrical) sensing and processing functions into a single neuromorphic device has become an important trend. Here, a flexible optoelectronic neural transistor with the channel region consisting of a one‐step spin‐coated tri‐blend film composed of 2, 7dioctyl[1]benzothieno[3, 2‐b][1]benzothiophene (C8‐BTBT), poly(3‐hexylthiophene‐2, 5‐diyl) (P3HT), and poly(methyl methacrylate) (PMMA). The device possesses broadband spectrum sensing and instant electrical‐processing capabilities.